Gut Microbiota Dysbiosis and Its Correlation with Viral Load in Chronic Hepatitis B Patients from Chennai, Tamil Nadu - M S, Nandini; K, Lakshmi; T, Shoba; Ramalingam, Shenbhagaraman (Bangladesh Journal of Medical Science, 2026)
Background Chronic hepatitis B virus (HBV) infection continues to pose a significant global health challenge, with viral load recognized as a crucial determinant of disease progression and prognosis. Growing evidence indicates that the gut microbiota plays a pivotal role in modulating immune responses and liver pathology through the gut– liver axis. Understanding microbial alterations associated with HBV viral load may offer insights into disease mechanisms and therapeutic opportunities. Materials and Methods A total of 104 participants were enrolled and categorized into three groups: healthy controls, low viral load HBV patients, and high viral load HBV patients. Clinical and biochemical parameters were recorded. Fecal samples were subjected to 16S rRNA gene sequencing to assess microbial diversity, taxonomic composition, and predicted functional pathways. Comparative analyses were performed across the groups to identify viral load–associated microbial changes. Results HBV-infected participants showed a marked reduction in gut microbial diversity compared to healthy controls. Notable taxonomic alterations included depletion of beneficial genera such as Faecalibacterium and Bacteroides, along with enrichment of potentially pathogenic Proteobacteria and Escherichia–Shigella. These changes were more pronounced in the high viral load group. Functional prediction analyses indicated significant disruptions in lipid metabolism pathways and an increase in bacterial cell wall biosynthesis processes, suggesting altered microbial functionality associated with disease severity. Conclusion The study demonstrates viral load–dependent gut dysbiosis in HBV-infected individuals, characterized by loss of beneficial commensals, expansion of pathogenic taxa, and functional metabolic disruption. These findings highlight the gut microbiota as a potential modifiable factor in HBV pathogenesis and support the exploration of microbiota-targeted therapies to enhance disease management. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S154-S158